Entrepreneurs skills for creating and managing IT projects - Sousa, M. J. (2018)
This article we will analyze the concept of entrepreneurship and the importance of skills development for entrepreneurs to create and manage IT projects. The problem studied in this research was to identify skills for developing an IT culture of entrepreneurship and the main objective was to build a model of skills development for IT entrepreneurs. To accomplish this research it was developed a search of articles based on the keywords "entrepreneurship" and "skills of IT entrepreneurs”, the period being considered between 2010 and 2014. The goal was to identify personal skills (cognitive, social and relational skills, technical skills and management skills) and business skills (strategies adopted by the company, products and/or services, corporate image, and management systems: human resource management, financial management, marketing, among others, and the formal and informal structure of the company). The literature review was based on entrepreneurship studies with the goal to identify soft skills that entrepreneurs need to develop to create and manage IT projects and to identify emergent technologies given the current economic challenges in order to create awareness of the possibilities for promoting the entrepreneurial activity.